Analysis Of Energy Saving And Consumption Reduction Technology In IOT Control System -Campus Energy Saving And Consumption Reduction Street Light System As An Example - et. al., Huacheng Huang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internet of things control technology is through the sensor technology, follow the prescribed protocol, the sensor data and network links, sensors through the network transmission data for identification exchange and networking, to achieve artificial intelligence, parameter identification, positioning, tracking, supervision and other functions. In the era of high-speed development, IOT control technology is a new control system model, is the era of artificial intelligence, driving the direction of economic development, is the focus of attention of people from all walks of life. The proposed Internet of Things control technology, coupled with the development of artificial intelligence technology is gradually rising, is the control system in the rapid development of high-tech industries. The development of society is inseparable from the construction of roads and energy saving and consumption reduction. The artificial intelligence technology of the Internet of Things (IoT) replaces the manual work monitoring, and can accurately and intelligently control and make a series of energy saving and consumption reduction. This paper discusses the IoT control technology based on the IoT campus energy saving and consumption reduction street lighting system.